Pilgrimage sites in Slovakia as the base for the formation of ecomuseums – case study of Ľutina pilgrimage site - Pasternák, Tomáš; Verba, Viktor (Geographica Pannonica, 2018)
Religious tourism is one of the oldest types of tourism and is connected with visiting various sacredplaces of religious significance. In Slovakia, the tradition of pilgrimage has rich history, as evidenced bya large number of pilgrimage sites that attract many pilgrims from Slovakia and abroad and still havetheir irreplaceable significance. However, these religious centres are not separated from other naturaland cultural-historical attractions, as they together form the genius loci of a particular territory. Theaim of this paper is to link the pilgrimage site with individual natural and cultural-historical interests inits surrounding in the context of the ecomuseum phenomena, which are now becoming more and moreaware of the inhabitants and local communities in individual regions. Linking these locations should improvepeople’s awareness of the territory they live in while making these places more attractive for visitors/pilgrims. Part of the paper is a case study on the example of the largest pilgrimage site of GreekCatholics in Slovakia – Ľutina, which has the largest potential to become a leader within a religioustourism and within a formation of ecomuseum in the region of eastern Slovakia in the context of implementationof projects and realization of activities directly in this pilgrimage site and surrounding attractive places.